Key labor law aspects of work-related stress - Molović Marija (Glasnik Advokatske komore Vojvodine)
In the paper, the author addresses significant labor law aspects of work-related stress, categorized as a type of psychosocial risk. This risk is defined as a biopsychological reaction of employees to continuous exposure to pressure, unreasonably demanding or extensive tasks, or other work-related efforts. The primary research problem involves identifying the various causes and consequences of work-related stress and the implications of failing to recognize this psychosocial risk on employee health. Although work-related stress is neither directly regulated by domestic legal provisions nor classified as an illness, it can significantly harm employees' health in multiple ways. The paper examines the concept of work-related stress, its causes, consequences, and possible legal and other preventive measures. It also highlights positive examples from other legal systems regarding prevention and protection from workrelated stress. The study identifies shortcomings in the domestic legal system and presents de lege ferenda proposals of importance for future amendments to existing regulations and practices. The research aims to confirm the hypothesis that work-related stress remains unrecognized and unmitigated in practice due to the absence of adequate legislation, posing a risk to employees' health, safety, and overall well-being. The study employs normative, axiological, and comparative law methods, alongside a survey and in-depth interviews with employees and employers.